PENINGKATAN PEMAHAMAN DAN KEMANDIRIAN BELAJAR MELALUI FLASHCARD PELAJARAN BAHASA MADURA PADA SISWA SEKOLAH DASAR - Sholehah, Amisha Mar'atus; Arifin, Zainal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was used to determine the influence of flash card learning media on students' understanding and learning independence at UPTD SD Negeri Lergunong 1 in Madurese language lessons. This study used a quantitative approach with a research design, namely one group pretest posttest design. The population in this study used all students of class 3B with a total of 25 students. The instruments used in this study were student learning comprehension questions and student learning independence questionnaires. While the analysis test used a validity test to see the validity of an instrument, a reliability test was used to see the level of consistency of a valid instrument, a normality test to determine whether the data distribution was normal or not, a paired sample t-test was used to compare the average of two variable data from one sample group, and the Manova test was used to analyze significant differences between the average of the dependent variable and 2 or more independent variables using the SPSS application. This is proven in the use of flashcard learning media in Madurese language lessons to improve students' understanding and learning independence. A significant value (2-tailed) of 0.0000 <0.05 was obtained, which states that there is an influence of flash card learning media on students' understanding and learning independence.